Carta Encíclica Laudato Si’: um diálogo com a ciência socioambiental - Siqueira, Antonio de Oliveira (2020)
Through this research it was possible to present the scientific basis behind the elaboration of the Encyclical Letter Laudato Si’, and additionally to understand its innovative character, not only by its contents, but also for all aspects involved in its preparation and disclosure. It was also evidente, and that was our initial hypothesis, the real possibility of dialogue between religion and science, faith and reason, demonstrating that there are conditions of cooperation between them, especially on themes closely related to the existence of the human being and its quality of life. These results were reached by means of research, analysis and comparisons among speeches made by the Catholic Church and the United Nations – UN; from the evaluation of pre-existing concerns related to the content found in the Encyclical Letter Laudato Si’ by the Cardinal Jorge Mario Bergoglio; from the presentation and comprehension of the Encyclical Letter Laudato Si’, and the analysis of an important quantity of early reactions after its publication; from the evaluation research of the sources and scientific references from the Encyclical Letter Laudato Si’ available in representative texts; and from the research about the subjects discussed in the Letter by specialists and academics, aiming to establish a critic evaluation of the document. It was also possible to understand that the Catholic Church’s address is in line with the one suggested by the UN, and they complement each other, even if sometimes there are apparent differences in the approach, despite the different response time dealing with environmental issues, and the more reactive than proactive characteristics of the UN and the Catholic Church. It was evident that Laudato Si’ wasn’t a casualty on the part of the Catholic Church and Pope Francis, deserving highlighting for the Fifth Episcopal Conference of Latin America (Conference of Aparecida) and its final document, because it evidenced that the Laudato Si’ was in conception, risking to say, even, that the Francis’ papacy started on that occasion